1972
DOI: 10.1111/j.1445-2197.1972.tb06743.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Radiological Assessment of Anal Continence in Childhood

Abstract: A simple numerical clinical method of scoring fœcal continence has been developed for use in children after repair of imperforate anus. A similar numerical score was then devised, using functional and structural parameters from a radiographic assessment of defœcation. Comparison of the two scores showed close correlation in the individual child, and the clinical score has been found to match closely the measured sphincter pressure at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 1 publication
1
50
0
Order By: Relevance
“…The mean Kelly's score [14] among our cases was 5.58 indicating good continence. On the other hand, constipation, which was a major contributing factor in our cases, improved postoperatively in cases presented with constipation and it did not complicate any of our cases postoperatively.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…The mean Kelly's score [14] among our cases was 5.58 indicating good continence. On the other hand, constipation, which was a major contributing factor in our cases, improved postoperatively in cases presented with constipation and it did not complicate any of our cases postoperatively.…”
mentioning
confidence: 46%
“…Incontinence didn't complicate any of our cases during the follow-up. The mean Kelly's score [14] was 5.58 ± 0.51 (range 5-6). Barium enema was done for all cases in our study 1 month after surgery and showed no colonic dilatation and no residual barium in their bowel [ Figure 5].…”
Section: Resultsmentioning
confidence: 99%
“…A number of clinical scoring system are currently in use to assess the functional and stooling pattern of children with ARM and HD. 12 The stooling outcome that we employed in this study were done using the recently proposed Krickenbeck scoring system. Though this was proposed for anorectal malformation, it has also been used in the evaluation of cases of HD.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and Altemeir and Martin and Caudill described careful clamp placement to entirely eliminate the rectal pouch. 12 Use of stapling devices for the colorectal anastomosis facilitate division of the common rectal wall.…”
Section: Introductionmentioning
confidence: 99%
“…12 The Kelly score introduced a quantitative scoring system based on functional and objective criteria. 13 Later, Holschneider and Metzer built on the concept of quantitative clinical scoring and added manometric parameters to the evaluation. 14 The Wingspread Score approaches the problem from a slightly different angle by gauging the functional outcome from the degree of therapy required for symptom control.…”
Section: Discussionmentioning
confidence: 99%